Comunicação breve: Rotational thromboelastometry and thromboelastography for patients undergoing surgical procedures: an indirect meta-analysis - André Soares Santos (Instituto Nacional de Assistência Farmacêutica e Farmacoeconomia, 2022)
Background: There is no consensus in the literature on the superiority between viscoelastic haemostatic assay (VHA) devices and several authors have performed meta-analyzes including them within the same group, assuming that their effects are similar. Objective: The objective of this study is to compare the efficacy of the protocols guided by rotational thromboelastometry with the protocols guided by thromboelastography for the control of the coagulation on patients undergoing surgical procedures. Methods: An indirect meta-analysis was conducted under a frequentist approach. Weights were calculated using the inverse variance method and adjusted using the DerSimonian and Laird random effects model. The measure of association used was the Odds Ratio (OR). All analyzes were performed in R. Results: No significant difference was observed between ROTEM® and TEG® in the indirect meta-analysis for the outcomes mortality (OR=0.6482, 95%CI=0.2213- 1.8984), acute kidney injury (OR=0.5282, 95%CI=0.0858-3.2522), thromboembolic events (OR=0.2759, 95%CI=0.0051-14.9529), reoperation for bleeding (OR=1.0719, 95%CI=0.3589-3.2013), risk of RBC transfusion (OR=1.0044, 95%CI=0.5346 to 1.8872), FFP (OR=0.6964, 95%CI=0.1258-3.8554), or platelets (OR=1.1956, 95%CI=0.4524 to 3.1597), or volume of RBC transfusion (MD=-0.0847, 95%CI=-3.6879 to 3.5185). Conclusion: No difference was observed between thromboelastography and rotational thromboelastometry in any of the outcomes included. This result suggest that they might be combined into a single meta-analysis. Nevertheless, there is much imprecision in the data for a robust conclusion.